Penerapan PJBL dalam Pengajaran Sakubun untuk pemelajar tingkat menengah - Hendri Zalman; Prisyanti Suciaty; Rita Arni; Maulluddul Haq (Omiyage : Jurnal Bahasa dan Pembelajaran Bahasa Jepang, 2023)
This article reports the findings of observations regarding the implementation of project-based learning (PjBL) in Intermediate Japanese Writing Courses (Chukyu Sakubun) at one university in Indonesia. The research instruments were observation and online questionnaire for 47 students who attended Chukyu Sakubun course. The project-based learning which is implemented in this course takes the form of a group writing activity with the output of the Tadoku reading books. The activity is divided into three stages: preparation stage, implementation stage, and evaluation stage. 15 tadoku books were produced with various genres. The results of the questionnaire explained that the majority of participants were actively involved in the process. Meanwhile, observation results show that during the project work process, students are able to communicate and collaborate with group members, as well as think critically and creatively in producing products.